Brain Waves Reflect Cognition-Emotion State as a Diagnostic Tool for Intervention in Dysfunctional States: A Real-World Evidence - Mayoral-Rodrígez, Sílvia; Pérez-Alvarez, Frederic; Timoneda-Gallart, Carme (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Objective: This study aims to characterize electrical signals to establish a diagnosis of cognitive-emotional dysfunction and guide a successful therapeutic intervention. Therefore, the present study aimed to observe these frequency bands in a sample of dysfunctional neurological behaviors to establish a neural marker of neural dysfunction that helps diagnose and monitor treatment. Methods: A descriptive retrospective (extracted from the database) observational study design based on real-world historical data from routine clinical practice. According to DSM-5, low academic achievement (n =70), disruptive behavior (externalizing behavior problems) (n=70), and somatic syndrome disorder (n=70) were the subjects. The mean age of the sample was 14.13 (SD = 1.46; range 12-18), 31.5% women. The measuring instrument was the NeXus-10, which is suitable for acquiring a wide range of physiological signals. Brain electrical activity was recorded by using the quantitative electroencephalograph (qEEG) in accordance with the 10-20 International Electrode Placement System. In particular, the specific form of miniQ (mini-qEEG) was used. Results: A pattern record present in all cases were identified. The record refers to (a) activity along the midline, namely, Fz-Cz-Pz, (b) activity from the center (Cz) to back, namely, Pz-O1 and O2, (c) activity from the center (Cz) forward (Fz), and (d) comparison between hemispheres. The characteristics of theta, alpha, and beta waves define the characteristic pattern of neurological dysfunction. The reversal of the dysfunctional pattern coincided with the remission of the clinical symptoms after treatment, which occurred in 87,6% of the subjects. We define remission as not meeting DSM-5 criteria. Conclusion: This study suggests that miniQ register could be considered a simple and objective tool for studying neurological dysfunction. This dysfunction is explained according to current neurological knowledge of interactive cognition-emotion processing. MiniQ may be a cheap and reliable method and a promising tool for the investigation in the field.